Hybrid Technique for Image Watermarking Using 3 Level LWT-Walsh Transform-SVD in YCbCr Color Space - Shafali Chachra, Rajeev Kumar, Rajesh Kumar (Mathematical Statistician and Engineering Applications, 2022)
Security is the prime concern in Industry Revolution 4.0. There are various techniques like watermarking, steganography and cryptography through which data can be secured so that unauthorized person unable to access prime data. This research paper is implemented using hybrid watermarking technique in YCbCr colour space to preserve the data secure from attacks. In this technique, both cover and host images are translated into YCbCr colour space from RGB image using specific command. After converting it into projected colour space three channels are generated and out of them one channel is selected for further processing. After selecting specific channel, three levels LWT (3-LWT) executed and images translated into four segments (HH, HL, LH, LL) as per frequency. After performing 3- LWT, WHT technique implemented followed by SVD to get projected output. The ultimate point of research is to get an appreciated PSNR value and its robustness against various attacks so that implemented integrated techniques do better with respect to other method. The experimental executed results from respective table depicts comparative analysis among proposed and existed method for parameter PSNR as well as processing time for embedding. It is clear from the above table III that the PSNR value of existing technique is 58.01 and proposed technique is 71.11. The value of processing time for extracting in existing technology is 0.766 second and proposed technique is 0.788 second. In term of PSNR from executed result it is clear indication that 3 Level LWT, Walsh Hadmard and SVD technique is superior than 2 Level LWT, Walsh Hadmard and SVD. Therefore, implemented method performs better in term of various parameters.